Eksplorasi kuskus pada hutan dataran tinggi di Lanny Jaya Pegunungan Tengah - Ranti, Febriza Dwi; Kawulur, Elda I. J. J. (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: The cuscus is a marsupial mammal, has a prehensile tail and fused second and third toes on its hind feet. Its distribution is in the highlands and lowlands. There is not much research on the types of cuscus in the highlands, therefore the aim of this research is to determine the type and morphology of cuscus in the Lanny Jaya Forest, Pegunungan Tengah, where the topography is the highlands. This research was carried out using observation methods in forest areas involving mammal hunters. The results of the research show that there are three types of cuscus in the Lanny Jaya forest area, namely Phalanger vestitus with the morphological characteristic of having thick hair on the dorsal part, gray in color with a wide central stripe on the prominent dorsal part. Phalanger carmelitae is often called mountain possum with its morphological characteristics of brown hair, no stripes on the dorsal and the tip of the tail being white. Phalanger sericeus is known as the silk-haired possum. This cuscus has dark golden brown hair, a narrow dorsal stripe and a dark tail. These three cuscuses are not found in the lowlands. Phalanger carmelitae is the largest cuscus while Phalanger sericeus has the smallest body size and body weight.